(untitled) (Geography and Tourism, 2019)
The issues pertaining to the impact of geopolitical situation on the development of international tourism, especially in the context of global uncertainty and international tension, are frequently discussed in scientific research. The paper seeks to test the author’s method of estimating the significance of geopolitical factor in relation to international tourism development through the use of Geopolitical Risk Index (GPR Index).The study shows that geopolitical risks adversely affect the development of international tourism, but do not inhibit the progress of the tourism sector as a whole. The results of the correlation analysis indicate a significant connection between the dynamics of global GPR Index and the changes in international tourist arrivals per annum. In order to assess the scale and nature of the impact of political events on international tourism, it is necessary to analyse not only the indicators of global GPR Index, but also GPR Index calculated for a particular country. Bearing that in mind, geopolitical situation proved to be a key factor in the Israel inbound tourism evolution in the 21 st century.